Physicochemical and microbial alterations in rumen liquor during Lantana camara toxicity in buffalo calves (Bubalus bubalis)* - Madial, R K; Randhawa, S N S (The Indian Journal of Animal Sciences, 2012)
Rumen liquor analysis of Lantalla camara intoxicated buffalo calves revealed complete absence of protozoal motility, concentration and idophillic activity with significant (P <: 0.01) increase in sedimentation activity test and methylene blue reduction time. However the glucose fermentation test value decreased significantly (P < 0,01). Significant (P < 0.01) increase in rumen pH (8.16±0.18) and ammonia nitrogen concentration (27.33±2.05 mg/dl) was also recorded during the toxicity. Total volatile fatty acid concentration decreased significantly (P < 0.01) to 9.06±0.88 m Eq/litre. It was concluded that Lantana camara var. aculeata caused gross rumen microbial inactivity in buffalo calves.